2015
DOI: 10.1007/s11017-015-9339-3
|View full text |Cite
|
Sign up to set email alerts
|

Towards a balanced approach to identifying conflicts of interest faced by institutional review boards

Abstract: The welfare and protection of human subjects is critical to the integrity of clinical investigation and research. Institutional review boards (IRBs) were thus set up to be impartial reviewers of research protocols in clinical research. Their main role is to stand between the investigator and her human subjects in order to ensure that the welfare of human subjects are protected. While there is much literature on the conflicts of interest (CIs) faced by investigators and researchers in clinical investigations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…This is consistent with the view put forward by Erde,11 and Kaur and Balan,12 who refute the notion that economic incentives are the sole cause of COIs 11 12. For example, Erde’s conceptualisation of COI takes into account non-financial interests, including practical concerns, such as a professional’s concern for their safety, emotional resources and time constraints; ideals, such as religious beliefs or professional indoctrination and predilections (ie, the disposition to value something negatively or positively) such as the fear of a particular outcome or those arising from relationships (eg, friendship or rivalry) 11.…”
Section: Defining Interests and Coissupporting
confidence: 90%
“…This is consistent with the view put forward by Erde,11 and Kaur and Balan,12 who refute the notion that economic incentives are the sole cause of COIs 11 12. For example, Erde’s conceptualisation of COI takes into account non-financial interests, including practical concerns, such as a professional’s concern for their safety, emotional resources and time constraints; ideals, such as religious beliefs or professional indoctrination and predilections (ie, the disposition to value something negatively or positively) such as the fear of a particular outcome or those arising from relationships (eg, friendship or rivalry) 11.…”
Section: Defining Interests and Coissupporting
confidence: 90%
“…Most authors have argued there is no meaningful conceptual and few practical differences between financial and nonfinancial COIs [12]. The two are often intertwined, influential, and require similar management [13,14]. Other authors have suggested that nonfinancial interests are virtually always present and should be considered an interest but not necessarily a conflict [15].…”
Section: Non-financialmentioning
confidence: 99%
“…Pharmaceutical companies have, therefore, used different marketing tools to draw physicians' attention to pharmaceutical products and influence the decisions made regarding adopting and using these products [14]. Some of the traditional marketing tools that pharmaceutical companies have used include product promotions, price, differentiation, and other incentives [15]. Some of the promotional techniques that pharmaceutical companies have used to maximize their profit margins are informed by two factors: the need to promote specific drugs; and the need to enhance company reputation through stronger relations with physicians [16].…”
Section: Introductionmentioning
confidence: 99%
“…As an effective way of promoting specific drugs, companies use drug advertisements mainly in formularies and medical journals. Other promotional tools used include presentation on new drugs at workshops and conferences, sending direct mails to physicians, sending MRs, and giving physicians free samples to distribute to patients [15]. One of the common approaches is the use of MRs, with the largest portion of the pharmaceutical budget for drug promotions being spent on this [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation